Calpain Dysregulation in Alzheimer's Disease. (16th October 2012) - Ferreira, Adriana
Abstract : Alzheimer's disease (AD) is characterized by the presence of senile plaques and neurofibrillary tangles in the neocortex and hippocampus of AD patients. In addition, a marked decrease in synaptic contacts has been detected in these affected brain areas. Due to its prevalence in the aging population, this disease has been the focus of numerous studies. The data obtained from those studies suggest that the mechanisms leading to the formation of the hallmark lesions of AD might be linked. One of such mechanisms seems to be the dysregulation of calcium homeostasis that results in the abnormal activation of calpains. Calpains are a family of Ca 2+ -dependent cysteine proteases that play a key role in multiple cell functions including cell development, differentiation and proliferation, axonal guidance, growth cone motility, and cell death, among others. In this paper, we briefly reviewed data on the structure of these proteases and their regulation under normal conditions. We also summarized data underscoring the participation of calpains in the neurodegenerative mechanisms associated with AD.